2017
DOI: 10.1016/j.vetpar.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Eimeria species occurrence varies between geographic regions and poultry production systems and may influence parasite genetic diversity

Abstract: HighlightsMultivariate analysis revealed comparable poultry clusters in north and south India.Eimeria species occurrence varied between system clusters.E. tenella occurrence across systems may underpin region-specific genetic diversity.E. necatrix was found to be more common in north than south India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 28 publications
11
34
1
Order By: Relevance
“…[5] (present study versus previous study: E. maxima, 6.92% versus 54.67%; E. tenella, 46.86% versus 80.67%; E. brunetti, 6.60% versus 44.67%; E. necatrix, 41.51% versus 68.00%). The three most prevalent species were E. mitis (78.57%), E. tenella (39.01%), E. necatrix (36.26%) in Henan (n = 182) and E. tenella (57.35%), E. mitis (50.74%), and E. necatrix (48.53%) in Hubei (n = 136); as reported by previous studies, the three most prevalent species E. tenella (67.30%), E. mitis (58.90%), and E. acervulina (45.80%) in North India were and E. tenella (57.50%), E. mitis (29.90%), and E. necatrix (14.90%) Southern India [25]. This may be because of differences in geographical conditions.…”
Section: Discussionsupporting
confidence: 81%
“…[5] (present study versus previous study: E. maxima, 6.92% versus 54.67%; E. tenella, 46.86% versus 80.67%; E. brunetti, 6.60% versus 44.67%; E. necatrix, 41.51% versus 68.00%). The three most prevalent species were E. mitis (78.57%), E. tenella (39.01%), E. necatrix (36.26%) in Henan (n = 182) and E. tenella (57.35%), E. mitis (50.74%), and E. necatrix (48.53%) in Hubei (n = 136); as reported by previous studies, the three most prevalent species E. tenella (67.30%), E. mitis (58.90%), and E. acervulina (45.80%) in North India were and E. tenella (57.50%), E. mitis (29.90%), and E. necatrix (14.90%) Southern India [25]. This may be because of differences in geographical conditions.…”
Section: Discussionsupporting
confidence: 81%
“…Fifteen birds sampled from location 1 included five from each of the indigenous Indian Aseel and Kadaknath breeds, supplemented by five commercial Cobb400 broilers for comparison. Fifteen birds sampled at location 2 duplicated those sampled from location 1, with the exception that Ross 308 commercial broilers were used instead of Cobb400, representing the local dominant-intensive commercial production systems [ 35 ]. All chickens were sampled at 42 days of age.…”
Section: Resultsmentioning
confidence: 99%
“…Demand for poultry meat and eggs is increasing dramatically, most notably in South Asia, where a mix of global commercial-type lines and indigenous chicken breeds are kept [ 35 ]. As efforts are made to improve the genetic merit of chickens, it is important to identify those genotypes best suited to the varied climatic regions and prevailing production systems, including those which favour a beneficial gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploring the risk factors associated with coccidiosis, Prakashbabu et al (2017) reported diversity in the distribution of Eimeria species according to poultry unit size, management and system within and between northern and southern India.…”
Section: Control Measure Of Coccidiosismentioning
confidence: 99%